2004
DOI: 10.7202/007360ar
|View full text |Cite
|
Sign up to set email alerts
|

Impact d’une stratégie d’intégration des TIC sur le sentiment d’autoefficacité d’enseignants du primaire et leur processus d’adoption d’une innovation

Abstract: Cette recherche-action vise le développement et la mise à l’essai d’une stratégie d’intégration des technologies de l’information et de la communication au primaire. Elle a aussi pour objectif l’analyse de son impact sur le sentiment d’autoefficacité des enseignants (volet quantitatif) et sur l’adoption de cette innovation chez ces derniers (volet qualitatif). Huit enseignants du primaire ont participé à cette recherche-action d’une durée de deux ans, tandis que neuf enseignants ont constitué le groupe témoin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
0
4
0
10
Order By: Relevance
“…Kebbell et al (1999) found that perceived utility was linked with the frequency of using the CI components. Self-efficacy (i.e., one's beliefs in one's ability to succeed to use a technique, which is to organize and to execute what is required to produce the expected results from the technique; Bandura, 1982Bandura, , 19912003) is also examined as some studies showed that it could also be involved in the adoption and the use of (new) 'techniques/technologies' (e.g., Burkhardt & Brass, 1990;Carugati & Tomasetto, 2002;Compeau & Higgins, 1995;Deaudelin, Dussault, & Brodeur, 2002;Hill, Smith, & Mann, 1987). In this study, we explore two other dimensions of acceptability proposed by several theoretical models and authors (e.g., Bubois & Bobbilier-Chaumon, 2010;Nielsen, 1993;Terrade, Pasquier, Reerinck-Boulanger, Guingouain, & Somat, 2009;Tricot, Plégat-Soutjis, Camps, Amiel, Lutz, & Morcillo, 2003).…”
Section: Aims Of the Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Kebbell et al (1999) found that perceived utility was linked with the frequency of using the CI components. Self-efficacy (i.e., one's beliefs in one's ability to succeed to use a technique, which is to organize and to execute what is required to produce the expected results from the technique; Bandura, 1982Bandura, , 19912003) is also examined as some studies showed that it could also be involved in the adoption and the use of (new) 'techniques/technologies' (e.g., Burkhardt & Brass, 1990;Carugati & Tomasetto, 2002;Compeau & Higgins, 1995;Deaudelin, Dussault, & Brodeur, 2002;Hill, Smith, & Mann, 1987). In this study, we explore two other dimensions of acceptability proposed by several theoretical models and authors (e.g., Bubois & Bobbilier-Chaumon, 2010;Nielsen, 1993;Terrade, Pasquier, Reerinck-Boulanger, Guingouain, & Somat, 2009;Tricot, Plégat-Soutjis, Camps, Amiel, Lutz, & Morcillo, 2003).…”
Section: Aims Of the Current Studymentioning
confidence: 99%
“…These are usability (i.e., the extent to which a technique can be used by specified users to achieve specified goals with effectiveness, efficacy, and satisfaction in a specified context of use; see Nielsen, 1993, for examples) and institutional acceptability (i.e., the extent to which the collective or individual representation of a technique is in agreement with the attitudes, norms, and values of the institution or the person; see also Nielsen, 1993, for examples). Self-efficacy (i.e., one's beliefs in one's ability to succeed to use a technique, which is to organize and to execute what is required to produce the expected results from the technique; Bandura, 1982Bandura, , 19912003) is also examined as some studies showed that it could also be involved in the adoption and the use of (new) 'techniques/technologies' (e.g., Burkhardt & Brass, 1990;Carugati & Tomasetto, 2002;Compeau & Higgins, 1995;Deaudelin, Dussault, & Brodeur, 2002;Hill, Smith, & Mann, 1987). More precisely, we examine if the interviewers' views on these attributes differ between the interview types, if they vary from before actually doing the interviews to after doing them, if they relate to the efficacy of the interviews, and if they correlate with the declared use of the techniques.…”
Section: Aims Of the Current Studymentioning
confidence: 99%
“…Ce constat relatif à une faible intégration des TIC soulève iné-vitablement la question de la formation pour utiliser efficacement les TIC dans leur enseignement (Hennessy, Ruthven et Brindley, 2005). Plusieurs études (Coulibaly et Karsenti, 2013;Deaudelin, Dussault et Brodeur, 2002;Skaalvik et Skaalvik, 2007) montrent que la motivation des enseignants est un facteur important dans le développement professionnel continu lié à l'intégration des TIC. Dans la section suivante, nous mettrons l'accent sur l'importance de la motivation dans le dévelop-pement professionnel.…”
Section: Obstacles Liés à L'intégration Des Ticunclassified
“…Validé dans plusieurs contextes (Deaudelin, Dussault et Brodeur, 2002), ce questionnaire a été utilisé pour mesurer les sentiments de compétence personnelle et générale.…”
Section: Traduction Et Adaptation Du Teacher Efficacy Scale Par Dussaunclassified
“…Ces enseignants semblent ainsi croire en leurs compétences, mais nier le pouvoir plus abstrait de l'école pour influencer le cheminement des élèves. À cet égard, nos résultats corroborent ceux de Deaudelin et al (2002). La différence non significative entre les moyennes de sentiment de compétence professionnelle générale des deux groupes peut s'expliquer par la définition du concept même de sentiment d'autoefficacité générale.…”
unclassified